Randomized Clinical Trial Comparing The Effect Of Oral Rehydration Therapy With And Without Racecadotril In The Management Of Acute Diarrhea In Children - Zulfiqar, Sughra; Zeb, Hifza; Mumtaz, Nadia; Khan, Ammara Musthaq; Sheikh, Taimur Khalil; Saeed, Tariq (Journal of Rawalpindi Medical College, 2023)
Objective: This study aimed to investigate the beneficial effect of racecadotril in children with acute diarrheal illness. Methods: This randomized case-control study was conducted at Watim General Hospital over four months from April to July 2023. A total of 120 children aged 3 months to 12 years with acute diarrhoea were included and randomly allocated to two groups. Group A (n=60) received standard treatment with oral rehydration therapy, while Group B (n=60) received oral rehydration therapy, zinc, probiotics, and racecadotril. The primary outcome measured was the mean duration of illness, and the secondary outcome was the number of stools 48 hours after the start of treatment. Data were collected using a pre-designed proforma and analyzed using SPSS version 24. Results: The study population had an average age of 50.35±41.52 months, with equal gender distribution. The mean duration of illness in Group A was 2.72±1.34 days, while in Group B, it was 2.70±1.29 days. There was no statistically significant difference in the mean duration of illness between the two groups (p=0.945). Conclusion: This study did not demonstrate a significant reduction in the mean duration of illness for children with acute gastroenteritis using standard treatment with or without racecadotril. Further investigations and large-scale studies may be needed to establish the efficacy of racecadotril in the management of acute diarrhoea in children. Keywords: Acute diarrhoea, ORS, Racecadotril.